1994
DOI: 10.1287/mnsc.40.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Electronic Integration in the Insurance Industry: An Empirical Test

Abstract: Electronic integration --

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
1
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 274 publications
(162 citation statements)
references
References 74 publications
2
156
1
3
Order By: Relevance
“…Choudhury (1997) observes that high market variability leads to multilateral IOS (e.g., electronic markets), whereas low market variability leads to electronic dyads or electronic monopolies. Zaheer and Venkatraman (1994) find that business process asset specificity and trust are positively associated with the degree of electronic integration, implying that IOS assets with high specificity lead to governance by electronic hierarchies rather than electronic markets.…”
Section: Figure 3 Relationships Investigated In Ios and Governancementioning
confidence: 86%
“…Choudhury (1997) observes that high market variability leads to multilateral IOS (e.g., electronic markets), whereas low market variability leads to electronic dyads or electronic monopolies. Zaheer and Venkatraman (1994) find that business process asset specificity and trust are positively associated with the degree of electronic integration, implying that IOS assets with high specificity lead to governance by electronic hierarchies rather than electronic markets.…”
Section: Figure 3 Relationships Investigated In Ios and Governancementioning
confidence: 86%
“…This seems consistent with Choudhury, Hartzel and Konsynski, (1998), who describe evidence from the chemical industry, where electronic markets are not widespread despite chemicals being an easily described commodity product. It is also related to early work that suggested that electronic markets will be used for products that are low in asset specificity and complexity of description, and electronic hierarchies for products high on both dimensions (Malone, Yates and Benjamin, 1987), an assertion supported by the empirical results of Choudhury, Hartzel and Konsynski, (1998), and Zaheer and Venkatraman (1994). Recent work in this direction (Granados, Gupta and Kauffman, 2005) finds that when asset specificity and product complexity are low, advanced IT facilitates the move from electronic hierarchies toward unbiased electronic markets.…”
Section: Introductionmentioning
confidence: 80%
“…The adoption of IOS: this literature has examined, among other things, the incentives for buyers and sellers to invest in IOS (Bakos, 1997), how asset specificity and trust influence IOS adoption (Zaheer & Venkatraman, 1994), the optimal ownership of IOS and the importance of network participants to asset productivity (Bakos and Nault, 1997), how external pressure and organizational readiness affect IOS adoption (Chwelos, Benbasat and Dexter, 2001), how the codifiability of transactions influences their suitability for B2B exchanges (Levi, Kleindorfer and Wu, 2003), and the impact of ownership on adoption and exploitation of IOS (Han, Kauffman and Nault, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…In other words, the buyer and supplier work together to create a shared infrastructure utilizing the Internet and other technologies as a means for commercial exchange. These systems are referred to as interorganizational information systems [50,51]. A traditional example is Electronic Data Interchange (EDI) [49].…”
Section: Self-service (Figure 3f)mentioning
confidence: 99%